(untitled) (Modern education and development, 2025)
Pharmaceutical biotechnology plays a crucial role in modern healthcare by providing advanced therapeutic options and personalized treatment approaches. Teaching this subject to nursing students enhances their understanding of biotechnology-based drugs, genetic engineering, and bio-pharmaceutical applications in patient care. This paper explores the significance of integrating pharmaceutical biotechnology into nursing education, its impact on clinical practice, and effective pedagogical strategies for teaching the subject.